Teacher Educator Professionalism and Student Teacher Learning in Nigerian Universities - Saheed Rufai; Adeola Oyenike Adeosun; Akinola Saliu Jimoh; Bello Musa (Indonesian Journal of Social Research (IJSR), 2021)
Of the three components constituting teacher education curriculum, namely general education, specialized education and professional education, the professional education component is arguably accorded the highest consideration in the scholarship of teaching. However, there is an emerging concern over the involvement of non-education specialists in the teaching of this component. Yet, there is little evidence of sufficient engagement with this concern in the Nigerian context. As a sequel to a study on pedagogical misconceptions by student teachers, this paper examines the impact of teacher educators' professionalism on student teachers' learning in Nigerian universities. Through the analytic method, the study engaged with data collected through the instrumentality of official records like Faculty brochures, lecture notes developed by teacher educators, systematic observations by the researchers, and semi-structured interviews involving selected participants. The qualitative study employs a constructivist paradigm that methodically situates data and analysis in the context of the experiences and perceptions of both the participants and researchers, and focusses on the main theme, namely teacher educator's knowledge as a predictor of student-teacher learning, which emerged from the data for the earlier study as collected in three universities where the present lead researcher assessed prospective teachers on teaching practice in their third and fourth years, in his capacity as teaching practice supervisor. In exposing the effect of teacher educator professionalism on prospective teacher learning, the present study revealed instances of miseducation by some of the teacher educators involved in teaching professional education courses, which substantially accounts for the student teachers' pedagogical misconceptions